A New Framework to Enable Equitable Outcomes: Resilience and Nexus Approaches Combined. Issue 6 (28th June 2018) - Stringer, L. C.; Quinn, C. H.; Le, H. T. V.; Msuya, F.; Pezzuti, J.; Dallimer, M.; Afionis, S.; Berman, R.; Orchard, S. E.; Rijal, M. L.
Abstract: Managing integrated social‐ecological systems to reduce risks to human and environmental well‐being remains challenging in light of the rate and extent of undesirable changes that are occurring. Developing frameworks that are sufficiently integrative to guide research to deliver the necessary insights into all key system aspects is an important outstanding task. Among existing approaches, resilience and nexus framings both allow focus on unpacking relationships across scales and levels in a system and emphasize the involvement of different groups in decision making to different extents. They also suffer weaknesses and neither approach puts social justice considerations explicitly at its core. This has important implications for understanding who wins and loses out from different decisions and how social and ecological risks and trade‐offs are shared and distributed, temporally and spatially. This paper conceptually integrates resilience and nexus approaches, developing a combined framework and indicating how it could effectively be operationalized in cases from mountain and mangrove social‐ecological systems. In doing so, it advances understanding of complex social‐ecological systems framings for risk‐based decision making beyond that which could be achieved through use of either resilience or nexus approaches alone. Important next steps in testing the framework involve empirical and field operationalization, requiring interdisciplinary, mixed method approaches. Key Points: We present a new framework bringing together nexus and resilience approaches Our new framework enables a more joined up approach to decision making and a focus on more equitable outcomes We show how our framework may be used in mountain and mangrove systems. Further empirical testing with field data is required